Article 31, 31 Years On: Choice and Autonomy as a Framework for Implementing Children's Right to Play in Early Childhood Services. (5th May 2021) - Colliver, Yeshe; Doel-Mackaway, Holly
Abstract: Article 31(1) of the Convention on the Rights of the Child (CRC) provides all children, everywhere, with the right to play. The CRC is the most widely ratified international human rights treaty, yet children's right to play is considered 'the forgotten right'. The widespread State inaction to fulfil this right could be partly due to continued uncertainty about how to define play. This Article argues for the application a large body of recent research with the group most qualified to determine whether activities are play or not: young children. This research demonstrates that choice and autonomy are two universal and essential indicia for an activity to be experienced as play. The Article contends that the fulfilment of young children's right to play would significantly increase if early childhood education and care (ECEC) institutions within States utilised these two indicia within daily programmed activities and in ECEC policies.